Performance comparison of multicast MANET CRN system’s based on POS scheme with different types of router protocol algorithms - Basma Nazar Nadhim; Sarab Kamal Mahmood (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
A multi-layer multi-hop mechanism, with one of three different types of router protocol algorithms (Steiner minimal tree (SMT), shortest path tree (SPT) and minimal spanning tree (MST)) was employed for the construction of multi-cast MANET CRNs. The probability of success (POS) used as the channel assignment scheme, is dependent on the availability of the channel, and the required transmission time. It was applied to the network after the conversion of the network’s random topology into one of the three algorithms (SMT, SPT or MST). This facilitated the selection of an efficient channel for the transmission of the CR user’s data, under the effect of the Rayleigh fading channel. Three idle probability circumstances (i.e., =0.1, 0.5, 0.9), and different network parameters, were used to compare the  performance of the CRN with three routing protocols in terms of throughput, and packet delivery rate (PDR). According to the simulation results, for a high traffic load of PUs ( 1) at different network parameters , the CRN with the SPT algorithm performed better than the CRN with the SMT or MST algorithm.